Re-vitalizing Law of Causation in the context of Contemporary World Economy (Bodhi Path, 2025)
Buddhism or Buddhist philosophy incorporates the teachings of Gautam Buddha, which mainly involves the system of logic and dialectic to find out the reality of all worldly phenomena and human life. The Buddha analysed and questioned the contradictions of existing social and spiritual thoughts of his time that gave birth to new idea or path leading to proper Salvation. The Buddha identified Aniccā/Anitya (Impermanence), Dukkhā/Duḥkha (suffering) and Anattā/Anātman (No – soul), the Trilakshan as three characteristics of existence. Anitya means impermanent nature of all the matters and phenomena (life, object, idea etc). Dukkha means suffering, the world which is full of suffering i.e. from birth to death, whatever lies within is suffering, which is also impermanent in nature. Anātman means No-soul, soul is a Vedic construct that guides and controls the nature of the life of a being, which can neither be manipulated, nor can be destroyed. However, the Buddha rejected this concept of soul as it is the karmic actions that colour the human consciousness which is responsible for all the activities that we perform and reap result accordingly. If a being is guided with right knowledge, it leads to perform good karmic activities and vice-versa. If there is something which controls our life and can be manipulated, then every being should be perfect and equal in size? However, it is clearly not so. Hence, karma and right knowledge are the driving force behind every fate of humans or all kind of living creature in nature. Thus, in order to understand the theory behind these regulations of different karmic forces, it seems appropriate to revitalize the understanding of the Buddhist theory of Law of causation or the Doctrine of Dependent origination or Paṭiccasamuppāda (in Pali) .Therefore, this Paper is yet an attempt to elaborate the doctrine of dependent origination in detailed manner and underline its relevance as an essential for contemporary world economy in order to achieve the Buddhist ideal of peace and prosperity in contemporary time by keeping in view the Primary text like Mahâvagga and several other secondary sources.
Keywords: Paṭiccasamuppāda; Buddhist economics; world economics; suffering; peace and prosperity